BY INORGANIC SUBSTANCES - Omonova Mahfuza (Galaxy International Interdisciplinary Research Journal, 2023)
First, simple substances are inorganic: they consist of atoms of one chemical element. For example, it is oxygen, gold, silicon and sulfur. However, this includes the entire periodic table.